CHALLENGES OF DIGITAL TRANSFORMATION IN THE VUCA ERA ON MICRO, SMALL AND MEDIUM ENTERPRISES: A SYSTEMATIC REVIEW OF THE LITERATURE - Elva Citra Sari; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
The era of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) has created a business environment that is very dynamic and full of uncertainty. This has an impact on the digital transformation carried out by Micro, Small and Medium Enterprises (MSMEs) so that they remain competitive and sustainable. However, MSMEs face significant challenges in adopting digital technology in this VUCA era. This research uses the Systematic Literature Review ( SLR ) methodology. By exploring relevant literature, this research aims to explore and synthesize the digital transformation challenges faced by MSMEs in the VUCA era based on existing literature. This SLR also explores potential strategies and solutions to overcome these challenges in the context of the VUCA era, such as flexible technology adoption, continuous digital skills training, and strategic collaboration and partnerships. The findings from this SLR provide valuable insights for policy makers, MSME support organizations, and academics to facilitate MSME digital transformation more effectively and sustainably in the challenging VUCA era.